BERBAGI KASIH DAN BERKAT ALLAH DENGAN KAUM MUDA - Ola Rongan Wilhelmus (Bahasa Indonesia, 2019)
All the talents, potentials and abilities possessed by young people are a gift and a blessing from God. Therefore the Church is always present for young people and is called to provide special assistance to them. The Church's efforts to provide assistance to the young people with the intention of helping them find meaning in life, realizing their talents, potential, abilities, dreams and life expectancy is a success of the Church in building the future of the Church, society and the world. Because the journey and future of the Church, society and the world are truly in young people.